Audiovisual bodygraphies and education: Designing vanishing lines for teachers’ masculinities from a sensitive pedagogy - Planella-Ribera , Jordi; Chiva-Bartoll, Oscar; Salvador-Garcia, Celina; Pallarés-Piquer, Marc (Fotocinema. Revista científica de cine y fotografía, 2022)
The purpose of this study is to analyze the experiences of a group of higher education students in order to understand how they lived the construction of masculinity during their formative stage. Through A/r/tography methodology, we analyzed, using a qualitative method based on a biographical and interpretative perspectives, 72 bodygrafies performed by students of the Master of Psychopedagogy of the Universidad xxx as part of an exercise in visual self-representation. The results of the analysis allowed us to identify two great pedagogies in the construction process of masculinities: an anesthetic pedagogy and other sensitive and/or resistance pedagogy. The results obtained from the analysis of visual narratives show valuable experiences that encourage critical dialogues, from which useful guidelines are derived in order to overcome educational practices that perpetuate the model of traditional masculinity. In this way, the text reveals, by using the visual arts, a latent social reality and rises the reflection on how to promote a critical and transformative citizenship that overcome the conceptions of masculinity of traditional archetype.